NOMINAL GROUP TECHNIQUE: DEVELOPING OF MUSIC APPRECIATION LEARNING ACTIVITY FRAMEWORK USING GUZHENG MUSICAL INSTRUMENTS TO HIGH SCHOOL STUDENTS IN CHINA - You Biyun; Azli Ariffin, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Music appreciation education is very important in secondary schools in China. There are even some educators who underestimate music education. The evaluation of the positive effects students receive from learning music is neglected to the point that no specific evaluation in the teaching process is made. The music learning process in China at this time is only based on the knowledge of the teacher. Teachers have a hard time getting students to appreciate, let alone appreciate, the music being taught. This leads to a low ability to appreciate music and the development of students' creativity. The purpose of this study is to design and develop a Music Appreciation Learning Activity Framework Using Guzheng Musical Instruments to High School Students in China. This research uses the Nominal Group Technique (NGT) as a method to collect data. The respondents for the study is nine (9) experts. The NGT process has helped researchers to develop a Music Appreciation Learning Activity Framework Using Guzheng Musical Instruments to High School Students in China. The developed framework shows the steps that students can take in the process of learning music appreciation using the Guzheng musical instrument. After going through this learning process, students finally become individuals who appreciate music.